PERFORMANCE OF AN ELECTROMAGNETIC LIQUID KRYPTON CALORIMETER - Fanti, V; Barr, G; Buchholz, P; Cundy, D; Doble, N; Gatignon, L; Gonidec, A; Hallgren, B; Kesseler, G; Lacourt, A; Laverriere, G; Linser, G; et al. (1994)
A prototype electromagnetic calorimeter containing 180 litres of liquid krypton has been tested in electron and muon beams at the CERN SPS. The main features of this detector are its active shower medium, a granularity of 2 cm with tower readout, and the use of the initial current readout technique with an effective shaping time of about 60 ns. An energy resolution for electrons of 4.1%/√E[GeV] with a constant term of 0.4% and a noise contribution of 50 MeV has been achieved. The calorimeter has a spatial resolution of 4.5 mm/√E[GeV] with a constant term of 0.3 mm and a time resolution of about 0.5 ns for energies larger than 10 GeV.